PELATIHAN KEPEMIMPINAN KENABIAN SEBAGAI PENDIDIKAN KARAKTER BAGI MAHASISWA - Alawiyah, Ela Minchah Laila; Hermahayu, Hermahayu; Sukmarani, Dhuta (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2016)
This study aims to determine whether Prophetic leadership training to improve character education in students at MuhammadiyahUniversity of Magelang. Subjects in this study are 22 subjects. The data collected and measured by using a modified propheticleadership scale, observation using anecdotal record, check list methods, and semi-structured interviews.The method in this study is experiment with the one Group Pretest-postest Design. Data analysis using wilcoxon signed rankstest. The comparison of character education on the students before the training (pretest) and after posttest known Sig 0,000value (sig value <0,05) which means hypothesis accepted The result of this study shows that Prophetic leadership training beable to improve the character education to students. The Students character education increased after the training.